Properties of Concrete Containing Recycled Fine Aggregate and fly ash - Ahmed, Shaikh (The Concrete Institute of Australia, 2011)
This paper reports the properties of concrete containing recycled fine aggregate (RFA) and fly ash (FA) obtained from local source in Perth, Western Australia (WA). This study is consisted of two parts. In the first part, the properties of concrete containing 25, 50, 75 and 100% (by wt.) replacement of natural fine aggregate (NFA) with RFA are considered. In the second part, the effect of class F fly ash as partial replacement of cement on the properties of recycled concretes containing 25% and 50% RFA are evaluated. The fly ash is used as 30% and 40% replacement of cement. The properties of concrete evaluated are the compressive strength, indirect tensile strength, flexural strength and water absorption. All properties are measured at 7, 28 and 56 days. The results show that, better compressive, tensile and flexural strength of concrete can be obtained in recycled aggregate concretes containing upto 50% RFA as partial replacement of NFA. However, in the case of recycled aggregate concretes containing 30% and 40% fly ash the compressive strength is increase at 56 days and both compressive strength and tensile strengths are decreased at early ages. The flexural strength is increased in recycled aggregate concrete containing fly ash. It is observed that the water absorption is increased as RFA content increased. It is also observed that the water absorption is decreased significantly in recycled aggregate concretes containing fly ash at 56 days.